Causal association between adiposity and hemorrhoids: a Mendelian randomization study - Huang, Jian; Gui, Ying; Qin, Hongping; Xie, Yubo (Frontiers in Medicine, 2023)
Background: Haemorrhoids are a very common anorectal disorder affecting a large number of individuals throughout the world. This study aimed to evaluate the causal effects of four adiposity traits including body mass index (BMI), body fat percentage, waist circumference, and waist-to-hip ratio on haemorrhoids by Mendelian randomization (MR). Methods: We used summary statistics of BMI (N=461,460), body fat percentage (N=454,633), waist circumference (N=462,166), waist-to-hip ratio (N=212,244), and haemorrhoids (N=337,199) from large-scale genome wide association studies of European ancestry. Univariable and multivariable MR were carried out to infer causality. The MR Steiger directionality test was used to test the causal direction. Results: The primary MR analysis using the inverse variance weighted (IVW) method showed that there were positive effects of genetically determined BMI (odds ratio [OR]=1.005, 95% confidence interval [CI]: 1.003-1.008, per standard deviation [SD], P=7.801×10−5), body fat percentage (OR=1.005, 95% CI: 1.001-1.008, per SD, P=0.008), waist circumference (OR=1.008, 95% CI: 1.005-1.011, per SD, P=1.051×10−6), and waist-to-hip ratio (OR=1.010, 95% CI: 1.003-1.017, per SD, P=0.003) on haemorrhoids. These findings were robust in multivariable MR adjusting for physical activity. The Steiger directionality test showed evidence against reverse causation. Conclusion: Our MR study supports a causal role of adiposity in the development of haemorrhoids. Adiposity prevention may be an important strategy for reducing haemorrhoids risk.